2021
DOI: 10.1007/s00259-020-05156-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity of second-generation tau PET tracers as biomarkers for Alzheimer’s disease in the context of a structured 5-phase development framework

Abstract: Purpose In 2017, the Geneva Alzheimer’s disease (AD) strategic biomarker roadmap initiative proposed a framework of the systematic validation AD biomarkers to harmonize and accelerate their development and implementation in clinical practice. Here, we use this framework to examine the translatability of the second-generation tau PET tracers into the clinical context. Methods All available literature was systematically searched based on a set of search term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 60 publications
0
33
0
2
Order By: Relevance
“…This work is part of a wider initiative, aimed to use the SBR and assess the validation status of biomarkers of tau pathology [25][26][27][28][29]. The initiative consisted of a workshop held in Geneva, November 11-12, 2019.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This work is part of a wider initiative, aimed to use the SBR and assess the validation status of biomarkers of tau pathology [25][26][27][28][29]. The initiative consisted of a workshop held in Geneva, November 11-12, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Four of the participant expert groups (viz., those led by Agneta Nordberg, Oskar Hansson, Rik Ossenkoppele, and Alexander Drzezga) have then assessed the validation status of CSF-, plasma-and imaging-tau AD biomarkers based on the evidence published until July 2020. Research strings and specific methods are reported in the five dedicated reviews [25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, a number of new ligands (second-generation tracers), purportedly with greater sensitivity and specificity, are currently under evaluation. Their level of maturity within the Strategic Biomarker Roadmap structure is summarized in the contributions by Wolters, Chiotis, and Bischof [5][6][7].…”
mentioning
confidence: 99%